Sustainable management in turfgrass systems: survivability during drought via minimal irrigation and simulating nitrous oxide emissions with process-based models - Hong, Mu (Kansas State University, 2022)
Reductions of water and nitrogen (N) inputs have long been important topics for sustainable turfgrass management. Facing rising challenges of water crises and climate change, more research is needed on such topics. With increasing city water shortages and water restrictions on turfgrasses in the U.S., it is important to research strategies to preserve C3 and C4 turfgrasses during prolonged drought. In addition, to guide the best irrigation and N-fertilization management strategies of turfgrass for the mitigation of global warming in this century, process-based models, such as DAYCENT and DeNitrification‐DeComposition (DNDC), become important tools, which simulate nitrous oxide (N₂O, an important greenhouse gas and ozone-depleting gas) and soil carbon sequestration. To find strategies for alleviating drought stress during prolonged drought with imposed water restrictions, the objectives in the first part of the dissertation were to (1) evaluate turfgrass performance during drought and recovery among irrigation levels, and (2) determine minimum water amounts for turfgrass during prolonged drought that allow for acceptable recovery. Two independent studies were conducted on C3 and C4 turfgrasses, respectively, using irrigation much lower than recommendation levels during 2 summers of drought under a rainout shelter. Results indicated that during severe drought and imposed water restrictions, minimal weekly irrigation of at least 20 to 30% reference evapotranspiration (ETo) and 40 to 50% ETo could reduce turfgrass damage and conserve water in zoysiagrass (C4; Zoysia japonica Steud., hereafter referred to as zoysia) and tall fescue (C3; Festuca arundinacea Schreb.), respectively. The failure of Kentucky bluegrass (C3; Poa pratensis L.) to survive extended drought was possibly related to being first-year sod. To inform and guide irrigation and N-fertilization management of turfgrass for global warming mitigation, the objectives of the second part of this dissertation were to 1) calibrate DAYCENT and DNDC for N₂O emissions from Meyer zoysia; 2) validate and test the two calibrated models and compare their prediction accuracies; and 3) predict long-term N₂O emissions, C sequestration, and global warming potential (GWP) of different irrigation and N-fertilization practices. A combination of global sensitivity analysis and a Bayesian method was used to calibrate DAYCENT and DNDC. After calibration, both models were validated using field measurements from two studies of zoysia. Validation results indicated DAYCENT (R² = 0.22 to 0.89; relative RMSE = 36 to 171%) outperformed DNDC (R² = 0.01 to 0.38; relative RMSE = 119 to 193%) in biweekly N₂O fluxes. Annual N₂O emission estimates obtained from validation of DAYCENT were within -49 to +26% of annual estimates interpolated from measurements, whereas DNDC simulations generally underestimated N₂O emissions by up to -86%. Results indicated DAYCENT, but not DNDC, can adequately simulate the impacts of irrigation and N-fertilization practices on N₂O emissions in C4 turfgrasses such as zoysia. When assuming no further climate change, the validated DAYCENT model predicted that the typically recommended N-fertilization and irrigation practice in fairway zoysia turf would reduce net GWP by encouraging soil carbon sequestration in the first 40 years of establishment, better than no N-fertilization, after which reducing N and water inputs would be beneficial in mitigating increases of N₂O emissions and net GWP. A medium global warming scenario would accelerate increases in N₂O emissions and GWP, especially with higher N and water inputs.
Keywords: Water conservation; Greenhouse gas emission; Global warming potential; Turf management